PENGEMBANGAN KURIKULUM DI SEKOLAH DASAR ISLAM TERPADU (Studi Situs di SDIT Assalamah Ungaran Kab. Semarang) - RUHADI , RUHADI (2011)
The purpose of this research is to determine curriculum development in SDIT Assalamah Ungaran with sub focus: curriculum design and implementation of curriculum development in SDIT Assalamah Ungaran. This type of research in this study used a qualitative research approach, in this study should not isolate the individual or organization into a variable or hypothesis, but should view it as part of a wholeness. The design of this research uses an approach called ethnography (ethnographic studies) in applying this model, the ethnographer in conducting field work to do making conclusions based on three sources: (1) From what people say. (2) From the way people act. (3) From the evidence that people use. Sources of data in this study is to document, diary, results of participant observation, depth interviews * with informants or research subjects, photos or videos, the collection of documents by performing a review of various references that are relevant to the research. Sources of data was also obtained from school principals, vice principals, teachers, staff, students. The data analyzed is the data associated with the management strategy of education by checking the validity of research data is the triangulation. The results showed that the development of curriculum in SDIT Assalamah can be known from two things: (1) Design curriculum development that combine curriculum with kurikulm Ministry of National Education Ministry of Religious Affairs. (2) Application of curriculum design to accommodate the curriculum that has been implemented namely by applying the "Full Day School System" and model-based learning "Multiple Intelligence", With an integrated curriculum design and development of good curriculum will impact the development of educational institutions, namely the quality of further education increases, able to reach many achievements to the national level, increasing public trust in the school, bringing SDIT Assalamah received the title of A in accreditation, and get the highest score A Semarang District and be able to print out put quality and highly competitive.